2002
DOI: 10.1046/j.1523-1755.2002.00665.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for elevated pulse pressure in patients on chronic hemodialysis: A case-control study

Abstract: At any MAP level, hemodialysis patients had a higher SBP, lower DBP, and higher PP values than those control subjects with a normal renal function who were matched for age, sex, diabetes mellitus, and body mass index. Further study is needed to determine whether preventing or reducing an elevated PP improves the prognosis for hemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 27 publications
2
25
2
Order By: Relevance
“…Tozawa et al (14) pointed out that the power of pulse pressure to predict total mortality was more accurate than that of SBP or DBP alone. London et al (12) described the importance of pulse pressure in considering BP control, and several studies reported that pulse pressure was an independent risk factor for CVE in the general population (25)(26)(27)(28)(29) and an independent predictor of risk for mortality or CVE in longterm HD patients (13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tozawa et al (14) pointed out that the power of pulse pressure to predict total mortality was more accurate than that of SBP or DBP alone. London et al (12) described the importance of pulse pressure in considering BP control, and several studies reported that pulse pressure was an independent risk factor for CVE in the general population (25)(26)(27)(28)(29) and an independent predictor of risk for mortality or CVE in longterm HD patients (13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have reported the relationship between pulse pressure and mortality or cardiovascular events in HD patients (13)(14)(15)(16)(17). In this study, we studied in a prospective cohort whether WAB was a more useful prognostic marker in HD patients than one-point BP measurement and investigated which components of WAB were the most potent marker in evaluating the effect of hypertension on cardiovascular events (CVE) or all-cause mortality in HD patients.…”
mentioning
confidence: 99%
“…Age and diabetes were significant predictors of elevated PP in both normal subjects and hemodialysis patients. A loss of compliance in large arteries is associated with aging, as described in the previous section, and diabetes accelerates the decrease in compliance of the vessel and stiffening of arteries results in increased PP (17). PP was extremely high in the majority of 37,069 patients who were undergoing hemodialysis and were analyzed by Klassen et al (18), with fewer than 10% of patients having PP Ͻ50 mmHg.…”
Section: Pp In Ckdmentioning
confidence: 99%
“…These authors showed that 50 mmHg likely was the reference value for PP in 61,724 ambulatory unselected individuals in France. Tozawa et al (17) reported that at any MAP level, hemodialysis patients had a higher SBP and PP and lower DBP values than control subjects who had normal renal function and were matched for age, gender, diabetes, and body mass index. The PP value in the control group was similar (49 mmHg) to the PP value in the group of Asmar et al (16).…”
Section: Pp In Ckdmentioning
confidence: 99%
“…At any mean arterial BP (MAP) level, patients on maintenance hemodialysis (MHD) have higher PP values than age-matched control subjects with normal renal function (6). Both increased arterial stiffness and PP have been associated with higher risks of cardiovascular events, all-cause mortality, and cardiovascular death in patients on MHD (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%